Investigating the influence of the extreme Indian Ocean Dipole on the 2020 influx of Red-necked Phalaropes Phalaropus lobatus in Kenya. (10th December 2021) - Nussbaumer, Raphaël; Gravey, Mathieu; Nussbaumer, Améline; Jackson, Colin
Abstract : Ocean currents have wide-ranging impacts on seabird movement and survival. By extension, the extreme oscillations they are subject to, such as extreme Indian Ocean Dipole (IOD) events, can also be expected to dramatically influence seabird populations. This study links the extreme IOD event that occurred in 2019–2020 to the unusually high number of Red-necked Phalarope sightings observed in February 2020. We show that the extreme IOD event resulted in low net primary productivity (a measure of plankton growth) offshore from the Somalia-Kenyan coast, where Phalaropes have been tracked in previous winters. We suggest that Phalaropes were therefore forced to move closer to the coast to find food at river estuaries, thus explaining the influx in February 2020. This study calls for closer monitoring of seabird populations in East Africa, particularly during extreme IOD events, which are expected to become more common in the future.